CFD-based Taguchi optimization of impeller geometry to improve centrifugal fan efficiency - Delima Yanti Sari; Bagas Santoso; Hendri Nurdin; Hastuti Hastuti; Rifelino Rifelino; Fitrah Qalbina; Tsung-Liang Wu; Dani Harmanto (Universitas Negeri Padang, 2026)
Centrifugal fans play a significant role in industrial ventilation systems. Their performance is affected by aerodynamic losses such as flow separation and non-uniform pressure distribution, thereby reducing the overall efficiency. Since design parameters influence the fan efficiency, design parameter optimization becomes one option for addressing this issue. Some optimization methods involve high computational cost and complex procedures. This raises the necessity for a more efficient and systematic optimization procedure. The aim of this study is to propose an integrated approach which involves Computational Fluid Dynamics (CFD) and the Taguchi method to improve the performance of a centrifugal fan. CFD is used to evaluate the performance of different design combinations, while the Taguchi method is used to optimize design parameters. The investigated design parameters are the inlet blade angle (β1), the outlet blade angle (β2), the number of blades (n), and the flow rate (Q). Each of the design factors has three levels, therefore, an L9 orthogonal array was utilized as the design of experiments. Analysis of variance (ANOVA) is used to determine their relative significance. The results show that the optimal combination of design parameters increase the efficiency from 39.79% (the reference) to 63.26%. The CFD simulations for the optimal combination exhibit the improved flow behaviour, which explains the enhanced efficiency. The results show the feasibility of the proposed method for improving the performance of the centrifugal fan.